2013
DOI: 10.1055/s-0033-1353240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Left Ventricular Diastolic Dysfunction in a Hispanic Patient Population

Abstract: Minimal data exist on attributes of diastolic dysfunction in the Hispanic population. The purpose of this study was to evaluate the prevalence and predictors of diastolic dysfunction in a Hispanic patient population. We performed a retrospective review of 166 consecutive echocardiograms in a southwestern Texas Hospital that caters to a large Hispanic patient population. We identified all echocardiograms that met criteria for diastolic dysfunction and assessed baseline demographics and comorbidities in the coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Thus the high prevalence of LVDD in the ECHO-SOL community based study population is surprising. Castro et al 34 reported on LVDD prevalence among Hispanics/Latinos in southwest Texas by doing a retrospective analysis of 166 consecutive echocardiogram from a hospital database. 129 of 166 (77.8%) were Hispanics/Latinos; 87 of 129 (67.4%) has some degree of LVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the high prevalence of LVDD in the ECHO-SOL community based study population is surprising. Castro et al 34 reported on LVDD prevalence among Hispanics/Latinos in southwest Texas by doing a retrospective analysis of 166 consecutive echocardiogram from a hospital database. 129 of 166 (77.8%) were Hispanics/Latinos; 87 of 129 (67.4%) has some degree of LVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of LVDD in a general population from previous studies [19,20,21,22] outside the African continent varied from 11.1 -67.4% depending on the population characteristics and diagnostic criteria. The prevalence in a German study [19] dropped to 3.1% when left atrial enlargement was considered.…”
Section: Discussionmentioning
confidence: 93%
“…Prolonged coronary occlusion can result in loss of anatomic integrity in the microvascular network and abnormalities in coronary microvascular function are known to cause ischemia even in the absence of epicardial stenosis [ 33 , 34 ]. Diabetes mellitus is also a well-established cardiovascular risk factor for the development of diastolic dysfunction [ 9 , 10 ]. Although we excluded diabetic patients from our study, our findings still show that an increased plasma glucose level is associated with worse diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the effects of age and hypertension might have already affected diastolic function parameters in the first measurement. In epidemiological studies in the general population, age and hypertension have previously been observed to be independent risk factors for deterioration of diastolic function [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation